Human resource communications - Pang, Joelle Si Ning (2008)
This study aims to explore the potential relationships between internal branding, internal communications and HRC, through interviews conducted with a group of 5 established multi-national corporations to provide insights on the methods and practices they have implemented as initiatives towards internal branding and enhanced communications, and the possibly correlated organisational success some of these MNCs enjoy.